Electromagnetic Simulation for THz Antenna-Coupled Microbolometers Operated at Room Temperature - Aoki, Makoto; Takeda, Masanori; Hiromoto, Norihisa (Makara Journal of Technology, 2013)
Room-temperature terahertz (THz) detectors with higher performance are necessary for utilizing the THz wave in various sensing, spectroscopy and imaging, but even the best ones in the present are still insufficient for the practical applications. This issue is essential especially in the region around 1 THz at which there exists a large technology gap between microwave and middle-infrared. Therefore, we study to develop an antenna-coupled microbolometer to achieve a high-performance THz detector operated at a room-temperature for sensing at around 1 THz frequency wave. In this paper, we present several important features and results obtained from electromagnetic simulations, which help to design a structure of the antenna and heater to absorb efficiently the power of THz wave.